Anthropometric assessment in retired geriatric population - Khan, AKM Hafiz Uddin; Latif, SA (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):154-8. The abstract of this article is available on the PubMed website